Smallholder farmers managing climate risk in India: 2. Is it climate-smart?. (February 2017) - Hochman, Zvi; Horan, Heidi; Reddy, D. Raji; Sreenivas, G.; Tallapragada, Chiranjeevi; Adusumilli, Ravindra; Gaydon, Donald S.; Laing, Alison; Kokic, Philip; Singh, Kamalesh K.; Roth, Christian H.
Abstract: Research about adaptation of crops to climate change at a regional scale is based on simplifying assumptions about current and future weather and about farmer management practices. Additionally, the impacts of adaptations are usually measured only in production terms and the feasibility of implementing proposed adaptations is rarely tested. In this study into adaptations of rice based cropping systems to future climate scenarios in Telangana, India, all adaptations were generated through participatory engagement, and were field-tested with local smallholder households in three villages as well as by cropping system simulation analysis. Adaptation options were first evaluated for historical climate variability, with outcomes assessed in terms of production, profitability and environmental consequences before they were evaluated as climate-smart adaptations to medium term climate change. In an earlier study, participatory intervention at household level was used to identify and evaluate new practices. These adaptations to climate variability were then tested with the cropping systems simulator APSIM on local historical weather data. Here we test the applicability of these adaptations to likely climate scenarios in 2021–2040 by using and statistically downscaling two contrasting global circulation models to generate contrasting climate change scenarios for each location. Adaptations were simulated with these future climate data sets and evaluated in terms of their gross margin, yield, yield stability, gross margin stability, global warming potential, greenhouse gas emissions intensity and, where irrigation treatments were varied, net water use, irrigation water productivity, contribution to the recharge of aquifers and nitrogen leached from the root zone. Compared with variability in historic yields the simulated yield changes in 2021–2040 climate scenarios were modest and their direction was dependent on the global circulation model used. Sustainability polygons were used to compare historic and future climate scenarios. These polygons clearly showed that adaptation options mostly resulted in trade-offs between productivity and environmental outcomes and between competing environmental outcomes. Results that were simulated for historic weather were strongly reflected in the two future weather scenarios, leading to the conclusion that participatory action research with smallholder farmers, coupled with field testing and simulation analysis can produce practical, sustainable and productive adaptations to climate variability that are also climate smart in that they are robust for future climate scenarios to 2021–2040. We propose that sustainability polygons may be a useful quantitative tool for analysis of the degree to which adaptations may be regarded as climate smart. Highlights: Potentially successful adaptations to baseline climate variability were found to be robust for 2020–2040 climate scenarios Sustainability polygons compare adaptations in terms of production, profitability and environmental consequences Competing adaptation options mostly resulted in trade-offs between productivity and environmental outcomes Sustainability polygons: a useful tool for discerning agricultural technologies' claims to being "climate smart"